Short-range ordering governs brittleness and ductility in W-Ta solid solution: Insights from Pugh's shear-to-bulk modulus ratio. (November 2021) - Liu, Honggang; Tang, Sai; Ma, Yunzhu; Liu, Wensheng; Liang, Chaoping
Abstract: In this work, the effect of short-range ordering on the intrinsic brittleness and ductility deduced from Pugh's shear-to-bulk modulus (G/B) ratio in W-Ta solid solution is investigated by first-principles calculation. The results show that the G/B value, an indicator of brittleness, decreases as a function of Ta concentration in W-Ta solid solution. The short-range ordered structure displays a ductile behavior in comparison to ideal solid solution and atomic segregated structure in terms of G/B value. This ductility of short-range ordered structure originates from the reduction of the number of partially covalent W-W bonds and a centrosymmetric screening of W-W interactions in W-Ta solid solution. Our findings suggest that short-range ordering should play a role in the solid solution softening and irradiation hardening phenomenon in W solid solution, and could be included in the future design of ductile W alloys. Graphical abstract: Image, graphical abstract